Enhancing fisheries education in Canada: The need for interdisciplinarity, collaboration, and inclusivity - Turgeon, Katrine; Hawkshaw, Sarah C.F.; Dinning, Kristin M.; Quinn, Brady K.; Edwards, Danielle N.; Wor, Catarina; Parlee, Courtenay E.; Debertin, Allan; Hawkshaw, Mike; Nelson, Benjamin W.; Zhang, Fan; Benestan, Laura M; et al. (PeerJ Preprints, 2016)
The Canadian Fisheries Research Network (CFRN) was initiated to increase interdisciplinary research capacity through enhanced, cross-sector collaboration. Training in the CFRN was important and unique for students because of the exposure to the realities of industry, government and academics working in close collaboration. As CFRN students, our goal for this paper was to assess whether Canada is appropriately preparing the next generation of fisheries graduates to tackle complex fisheries management problems. This assessment consisted of 1) a systematic review of fisheries-related education across Canada, 2) a reflection on our experience in the CFRN, and 3) comments on the importance of inclusive and interdisciplinary approaches in fisheries education and fisheries research. Based on our assessment, we concluded that the availability of fisheries education in Canada is limited, particularly with respect to interdisciplinary training. We contend that the CFRN enhanced our educational experience by fostering interdisciplinary and inclusive fisheries research. We recommend that the CFRN model be considered both in the development of fisheries education initiatives and in the design of future fisheries research.
Keywords: Education; Interdisciplinarity; Fisheries; Network; Fisheries research; Natural sciences; Social sciences; Canada; Policy; Fisheries management